Government Relations and Interventional Radiology - Englander, Meridith J. (Seminars in Interventional Radiology, 2023)
Health care policy in the United States is made by nonphysician lawmakers and government employees. Through advocacy and lobbying, physicians have an opportunity to be involved in the process. Interventional radiologists (IRs) are the experts on issues related to IR. Government relation offers IRs the opportunity to engage with members of Congress, officials in Federal and State agencies, and State legislators to inform and influence their decision making. The Society of Interventional Radiology PAC (SIRPAC) is the only PAC to represent the interests of interventional radiology. Increased contributions to SIRPAC are essential to be sure that the voice of IR is heard.
Keywords: advocacy; Medicare; SIRPAC; government; interventional radiology